Creating Rights, Terminating Rights, Overcoming Legal Conflicts - Roy Andrew Partain (The Constitutional Court of the Republic of Indonesia, 2022)
At the heart of this paper are judges and their obligations to ensure that conflicts over fragmented rights are cured, that fundamental rights are stewarded, and that justice prevails. There are several respected legal theories that have never been examined together before, but when three of them are placed in a nexus of constitutional law, we find that these ideas support broad powers for courts to control the distribution and allocation of rights, enabling the resolution of conflicts at many social levels. First, a succession of scholars has identified the risks of ‘fragmenting rights’, of allocating overlapping rights to too many parties. The danger presented is that those rights-holders may lose the use of their legal rights or privileges; this outcome is known as the ‘Tragedy of the Anticommons’. Too many rights held by too many parties, a ‘fragmentation of rights’, can lead to a lack of access to rights and a lack of access to justice. Second, the legal theories of Nobel Laureate Ronald Coase, who found that initial allocations of rights across a community might have been allocated in a manner that frustrates negotiations and other means to avoid conflicts; but judges have an opportunity and an obligation to reset those allocations of rights to better enable society toflourish. Third, Yale constitutional scholar Robert Cover wrote that judges can and should terminate claims of overlapping rights so that the litigious parties, and society at large, can return to a more harmonious co-existence. Cover wrote that this methodology of ‘jurispathic’ judges was both an ethical and a robust means of solving Dworkin’s ‘hard cases’. This paper investigates the nexus of these three jurisprudences and what the impact of their nexus is for constitutional scholars. This paper delivers original theoretical legal findings and provides functional approaches to best enable the resolution of conflicts before courts and the maintenance of rights and privileges for all parties. This paper documents an argument that courts, especially constitutional courts, have more power to solve social conflicts and other conflicts arising from legal rules and culturesthan many constitutional law scholars may have previously assumed feasible.